Mutual funds withdraw shield: performance or agency costs driver? - Alves, Carlos (2014)
In this paper, using a unique database, we compare the performance of a set of equity mutual funds to a set of equity savings funds, which are similar to equity mutual funds in all but one characteristic: the tax regime that strongly penalizes withdrawals from equity savings funds. We found evidence consistent with the hypothesis that mutual funds less subject to liquidity shocks exhibit higher performances.